PEMBELAJARAN DARING BERBASIS METODE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK OPTIMALISASI NILAI KOGNITIF PESERTA DIDIK - Sari Kartini; Hening Widowati; Triana Asih (Bioedukasi Jurnal Pendidikan Biologi, 2020)
Theachers in the millennial era are expected to start using digital tools that can increase discussion activities and material is e-learning so that they can optimize the cognitive value of their students. The purpose of this research is to optimize the cognitive value of students through learning based on the TAI method. This research method uses experiment or experiment (experimental research) using the t-test. The results of the study the average learning outcomes of students through learning based on the TAI method were more than the average learning outcomes of students through conventional learning processes, which means e-learning learning so that it can optimize the cognitive value of class X MIA students at Senior High School N 1 Kibang.:  Kata Kunci :Daring, TAI, Nilai Kognitif.